(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The trophic activity of Zyginidia pullula, Empoasca vitis and Graphocephala jennahi was examined on host-plants and on liquid and agarized artificial diets. Z. pullula emptied the leaf parenchyma of Zea mays in the area surrounding the point of stylet penetration, E. vitis reached the phloem of Actinidia chinensis and Vitis spp. but not that of Alnus glutinosa, G. jennahi involved the xylem-tubes of ornamental Rhododendron. In artificial diets, stylet tracks appeared branched in Z. pullula, linear in E. vitis and G. jennahi. Salivary sheaths of Z. pullula showed affinity for a basic dye, those of E. vitis reacted with an acid dye, those of G. fennahi stained with both kinds of dye.